INSTALLATION OF PASTEURIZATION DAIRY CATTLE EQUIPMENT BASED ON BIOMASS ENERGY: WOOD SAW DUST BRIQUETTES - Sugiono sugiono (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2016)
Often the location of dairy cattle farms is far from KUD shelter/processing becomes a real obstacle to maintain the quality of milk from a review of health. Moreover, the problems of availability of non-renewable energy for small entrepreneurs is burdensome in terms of price. Potential utilization of the Tepas village becomes an important things to synergize between the workman of wood cutter and the farmers of dairy cattle. Therefore, this journal aims is to create a pasteurization tools fueled of woodsawdust briquettes. The first step is studying literature and field surveys which is used as a basis in designing the briquette molding equipment and hearth of pasteurization in the model of 2D / 3D CAD design. The next step is making dough of woodsawdust with adhesive starch and then pressed by briquettes molder. The briquettes which have finished is used as a heat source of pasteurization tube with LTLT (Low Temperature Long Time) methods to reach temperatures of 650°C within 30 minutes. Pasteurized milk can be stored at room temperature within safe 3 days which means could saving the transportation fuel around Rp. 740,000, - per month.